Ovarian torsion in early pregnancy: a rare case of twisted functional cysts with preserved pregnancy - Abdelmajide, Regragui; Marouane, Boukroute; Taheri, Hafsa; Saadi, Hanane; Mimouni, Ahmed (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ovarian torsion during early pregnancy is a rare but critical surgical emergency. We present a case of a 28-year-old G6P4 patient at 7 weeks gestation who presented with acute pelvic pain and was diagnosed with bilateral ovarian torsion secondary to functional cysts. Ultrasound revealed two large cysts (57 mm and 49 mm) with characteristic "whirlpool sign." Emergency laparoscopic detorsion and cystectomy were performed, preserving ovarian tissue and maintaining the pregnancy. Postoperative management included progesterone support with favorable outcomes at 2-month follow-up. We review the pathophysiological mechanisms predisposing to torsion in early pregnancy, including β-hCG-induced cyst formation and increased adnexal mobility. The discussion emphasizes that ovarian preservation should be attempted even in cases of apparent ischemia, as functional recovery is often possible. This report adds to the limited literature on bilateral torsion in pregnancy and demonstrates that excellent outcomes can be achieved with timely, minimally invasive surgery combined with appropriate hormonal support.